Students’ Difficulties in Stressing Four-Syllable Words: An Exploratory Study at the English Department, Hamzanwadi University - Rohmi, Ni’matur; Marzuki, M. Junaidi; Agustina, Yulia; Husnu, Muhammad (IKIP Siliwangi, 2026)
This study aims to explore the ability and awareness of students regarding word stress, specifically on four-syllable words. The subjects of this research were eight fourth-semester students from the English Language Education study program who had completed the morphology course. The participants were randomly selected from various classes. This study employed a qualitative approach using semi-structured tests and interviews as data collection methods, conducted in person. The findings indicate that most participants have limited ability in correctly placing word stress on four-syllable words. Common errors occurred due to a lack of understanding of morphological rules, especially those related to prefixes and suffixes that influence stress placement. The participants' awareness of the importance of word stress in communication also varied; some were aware of its function, while others considered it insignificant. The study concludes that despite having received morphology instruction, students still face challenges in applying the concept of word stress practically. The implications of these findings highlight the need for a deeper focus on word stress exercises, particularly in the context of phonology and morphology, to enhance students' skills and awareness in English pronunciation.